2022
DOI: 10.3390/insects13020167
|View full text |Cite
|
Sign up to set email alerts
|

The Resistance of Seven Host Plants to Tetranychus merganser Boudreaux (Acari: Tetranychidae)

Abstract: Red spider mites, Tetranychus merganser Boudreaux (Acari: Tetranychidae), is an agricultural pest that causes economic losses in papaya and nopal crops in Mexico. The aim of this research was to assess antibiosis and antixenosis as resistance mechanisms in seven host plants (Thevetia ahouai, Carica papaya, Phaseolus vulgaris, Moringa oleifera, Pittosporum tobira, Helietta parvifolia, Capsicum annuum var. glabriusculum) to red spider mites. Antixenosis was evaluated by non-preference for oviposition and feeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Other studies have reported that the number of eggs laid by T. merganser is related to the host plant [ 24 , 25 ]. Chacón-Hernández et al [ 24 ] reported lower oviposition of T. merganser female (66.00 ± 15.31, 66.33 ± 8.67 and 44.33 ± 21.40) on three accessions (BGH-425, BGH-426 and Ch1) of C. annuum var.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Other studies have reported that the number of eggs laid by T. merganser is related to the host plant [ 24 , 25 ]. Chacón-Hernández et al [ 24 ] reported lower oviposition of T. merganser female (66.00 ± 15.31, 66.33 ± 8.67 and 44.33 ± 21.40) on three accessions (BGH-425, BGH-426 and Ch1) of C. annuum var.…”
Section: Discussionmentioning
confidence: 99%
“…Chacón-Hernández et al [ 24 ] reported lower oviposition of T. merganser female (66.00 ± 15.31, 66.33 ± 8.67 and 44.33 ± 21.40) on three accessions (BGH-425, BGH-426 and Ch1) of C. annuum var. glabriusculum than on P. vulgaris (166.00 ± 7.23) at 120 h, under laboratory conditions at 27 ± 2 °C, 60–70% RH and a photoperiod of 12:12 L:D; meanwhile, Treviño-Barbosa et al [ 25 ] reported that the daily oviposition rate of the red spider mite was higher in C. papaya (7.46 ± 0.18 eggs/female/day) than on P. vulgaris (4.41 ± 0.22), M. oleifera (3.57 ± 0.12), C. annuum var. glabriusculum (2.92 ± 0.12), H. parvifolia (1.49 ± 0.04), P. tobira (1.10 ± 0.09), and T. ahouai (0.97 ± 0.09) at 28 ± 1 °C, 70–80% relative humidity and photoperiod of 12:12 L:D. These variations could be attributed to differences in plant species and cultivar types, as they may have differences in nutrient content, morphological characteristics and in secondary metabolite levels, as well as environmental factors [ 26 , 35 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations